Peningkatan Pengetahuan Juru Pemantau Jentik Anak Sekolah di SMP 5 Kabupaten Sragen - Sudaryanto, Agus; Dewi, Shinta Kurnia; Ainnurriza, Ulfiana Savira; Pratiwi, Rini Indah (Civiliza Publishing, 2024)
This community service is based on the high number of dengue fever in Sragen district. The endemic problem of dengue fever in Sragen Regency can be reduced by maximizing mosquito eradication efforts and maximizing the role of the function of mosquito larvae monitors (Juru Pemantau Jentik/Jumantik). Education program about mosquito larvae monitors from school children was chosen to increase the number of mosquito larvae monitors with students of SMP Negeri 5 Sragen as the target. This community service was carried out in January 2023 with 100 participants consisting of 65 women and 35 men. This activity was carried out by providing counseling through video screenings. The results of the community service illustrate the average value of knowledge after the counseling, which was 83.38 with a median of 84.00. It is hoped that the Jumantik counseling activities for students can raise awareness and increase knowledge so that efforts to monitor mosquito larvae in Sragen Regency increase so that a movement to eradicate dengue fever arises.